Hak Politik Penyandang Disabilitas di Angkola Selatan - Nasution, Nurul Fitria; Nasution, Muhammad Arsad (Jurnal El-Thawalib, 2021)
Persons with disabilities are any person who experiences physical, intellectual, mental, and/or sensory limitations in the long term who in interacting with the environment can experience obstacles and difficulties to participate fully and effectively with other citizens based on equal rights. This equality of rights includes the right to participate in politics as an example of political rights for persons with disabilities, namely to participate in general elections. Based on Article 13 of Law No. 8 of 2016 states that one of the political rights for persons with disabilities is the right to vote. In the case of elections, the general election commission becomes an institution that is responsible for the course of elections that occur in an area. In the South Angkola sub-district which is part of South Tapanuli, there is a South Tapanuli General Election Commission which is the institution in charge of the general elections in South Angkola sub-district. Based on research, it shows that the South Tapanuli General Election Commission as the organizer of the election in the South Angkola District area has made several efforts to fulfill political rights for people with disabilities in South Angkola District in organizing the general elections for the Regent and Deputy Regent. The efforts made by the General Election Commission of South Tapanuli are in accordance with Law No. 8 of 2016 on Persons with Disabilities by upholding the values of equality and equal opportunity for persons with disabilities to participate in the world of politics. The South Tapanuli General Election Commission in its implementation carried out fulfillment of the political rights of persons with disabilities in the General Election, making efforts such as, conducting special data collection for voters with disabilities, getting socialization about equal political rights for persons with disabilities in General Elections, Obtaining TPS that appropriate, obtaining special ballots and providing assistance for persons with disabilities to facilitate the delivery of political rights.‎